Co-Generation Technology For High Efficiency Conversion Of Natural Gas Energy In Indonesia - D.A. Ismukurnianto (Scientific Contributions Oil and Gas, 1998)
Very high efficiency energy conversion of natural gas can be obtained by simultaneous production of electricity and thermal energy. In industrial countries, this technology has been widely used in various industries, such as pulps, foods, oil refineries, and chemical industries. Moreover, it is becoming very popular and spans a wide spectrum of market, from the relatively small-scale residential and commercial consumers to large industrial plants.In Indonesia, this technology has an open opportunity for application, particulary in support of the countryâ€™s energy conservation and â€œblue skyâ€ programmes. There are obvious reasons of using this technology, the reduction of fuel consumption of about 75%-80%, and the exces electricity production can be sold to the public utility.This paper will generally discuss the technology of gas co-generation, including its characteristic, and the economic and environmental considerations of using gas co-generation in Indonesia.